1991
DOI: 10.3354/meps078285
|View full text |Cite
|
Sign up to set email alerts
|

Omnivorous feeding by planktotrophic arvae of the eastern oyster Crassostrea virginica

Abstract: In order to better understand the particle diet of planktotrophic larvae of the eastern oyster Crassostrea virginica (Gmelin) we measured their ingest~on of naturally occurring food organisms. By using a dual radioisotope (3H and I4C) label~ng technique in conjunction w~t h plankton size fractionation procedures we demonstrate that oyster larvae feed upon bacteria, phagotrophic protozoans and phototrophs present in the diverse summer plankton assemblages of Chesapeake Bay, USA. Prodissoconch I1 oyster larvae c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 37 publications
(54 reference statements)
3
23
2
Order By: Relevance
“…Previous studies have suggested the importance of picoplankton in the diet of bivalve larvae as well as bacteria and detritus (Baldwin and Newell 1991;Raby et al 1997;Sommer et al 2000). However, for this study, the contribution of picoplankton to the carbon ingested by the larvae is extremely small.…”
Section: Discussioncontrasting
confidence: 39%
“…Previous studies have suggested the importance of picoplankton in the diet of bivalve larvae as well as bacteria and detritus (Baldwin and Newell 1991;Raby et al 1997;Sommer et al 2000). However, for this study, the contribution of picoplankton to the carbon ingested by the larvae is extremely small.…”
Section: Discussioncontrasting
confidence: 39%
“…Growth of oysters was always positive, but did not follow the temporal or treatment-related patterns of integrative measures of their phytoplankton prey. Unlike Macoma, growth of the oysters showed no significant relationship to phytoplankton production or biomass, or to particulate N or C. Studies have shown that although oysters can ingest a variety of particle types and sizes, the nutritional value can vary greatly among prey types (e.g., Crosby et al 1990;Newell 1990, 1996;Baldwin and Newell 1991). Growth rates of oysters therefore vary greatly with species and biochemical composition of the available phytoplankton, bacteria, and other particulates.…”
Section: Discussionmentioning
confidence: 99%
“…The oyster is a key epifaunal species throughout Chesapeake Bay, occurring on and forming hard substrate. It is a suspension-feeder feeding principally on phytoplankton but capable of ingesting other food such as detritus and attached bacteria Crosby et al 1990;Baldwin and Newell 1991;Kennedy et al 1996). Macoma is an infaunal species found in both muddy and sandy environments.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by Newell & Jordan and Newell & Langdon [31,32], by active selection, oysters are able to sort organic material by size before ingestion while rejecting inorganic particles. Baldwin & Newell and Baldwin [50,51] reported that many bivalves like Crassostrea are able to discriminate the nutritional quality of preys and sort foods according to their nutritional needs. Consequently, non-nutritious particles are sorted and rejected before entering the gut, while nutritious foods are retained in the stomach and undergo digestion process.…”
Section: Discussionmentioning
confidence: 99%